(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Background: Anterior cruciate ligament injury is one of the most common knee injuries, with approximately 250,000 ACL tears occurring in the United States per year. Historically, ACL injuries were described by ancient Egyptians in the famous Smith Papyrus (3000 BC). Hippocrates also (460– 370 BC) mentioned the subluxation of the knee joint with ligament pathology. However, the Greek physician Claudius Galen was the first to describe the true nature of the ACL. Synthetic grafts had been postulated to have both biological and biomechanical significance to induce new tendon synthesis around pure carbon scaffold. This was experimented in animal models by group from Cardiff during 1970s and 1980s. Giving the promising results; they shifted for human clinical trials which showed sinus formation over graft material as an only reported complication after maximum three years follow up. However, Rushton et al. reported complications for ten of thirty-nine patients who underwent synthetic carbon- fiber graft ACL reconstruction. These were synovitis, staining of cartilage and menisci and thin formed fibrous sheath around the graft alongside with the previously described skin ulceration over graft’s securing knots. This valuable study was published in 1983.